Offspring of male rats exposed to binge alcohol exhibit heightened ethanol intake at infancy and alterations in T-maze performance - Hollander, Jessica (2019)
Alcohol use is associated with a variety of negative consequences, including heightened likelihood of cognitive impairment, proclivity to alcohol use disorders (AUD), and alterations in the drinker's offspring. Children and rodents exposed to alcohol during pregnancy, or those whose fathers consumed alcohol prior to mating, often exhibit neurodevelopmental, physiological, and behavioral deficits. The present study assessed cognitive function and alcohol intake in male and female rats that were offspring of alcohol-exposed fathers. Adult male rats were exposed to alcohol or vehicle (0.0 or 2.0 g/kg, respectively; twice daily for 2 days followed by a rest day, for a total of eight alcohol or vehicle exposure days), or were left untreated and then mated with non-manipulated females. The offspring were assessed for alcohol intake, via intraoral infusion, followed by cognitive assessment via an alternating T-maze task. The results indicated that paternal ethanol exposure, prior to breeding, resulted in offspring that consumed significantly more ethanol than vehicle or untreated controls. Furthermore, the offspring of alcohol-exposed fathers exhibited a significant failure to initiate and complete the T-maze performance tests. Although, when they did engage in the tests they performed at the level of controls (i.e., 80% correct). The present results add to a growing body of literature suggesting that paternal pre-conception alcohol exposure can have deleterious effects on the offspring.